MEMAHAMI FILSAFAT PANCASILA SEBAGAI PANDANGAN HIDUP IDEOLOGI & DASAR NEGARA - Hutabarat, Dany Try Hutama; Sutta, Roffi Rivaldo Arya; Wardana, Wahyu Habib; Fadila, Zahra Nur; Sapahira, Prety; Tanjung, Rani (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study aims to understand the philosophy of Pancasila as a view of life, ideology, and the basis of the state. The influence of globalization is unavoidable. Globalization makes all countries into unlimited countries. Pancasila is needed to filter the influence of globalization. In today's era, the meaning of Pancasila has been forgotten by some people in Indonesia. The process of formulating Pancasila even though it was a very long process. Pancasila is a guide in the life of the nation and state. Therefore, Pancasila is referred to as a view of life, ideology and the basis of the state. The structure of Pancasila itself shows a series of tiers in which each precept has its own place in the unity, so that it cannot be changed anymore. Pancasila is the basis for regulating the administration of a country's administration in the fields of ideology, politics, economy, socio-culture, defense and state security.